2021
DOI: 10.5005/jp-journals-10071-24052
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-demographic and Outcome Predictors in Solid Tumor Patients with Unplanned Intensive Care Unit Admissions: An Observational Study

Abstract: A bstract Objectives Critically ill solid organ malignancy patients admitted to intensive care unit (ICU) as unplanned medical admissions behave differently from other subsets of cancer patients (hematolymphoid malignancies and cancer patients admitted for postoperative care). These patients if appropriately selected may benefit from the ICU care. There is paucity of data on critically ill unplanned admissions of solid organ malignancies from South Asia. We analyzed data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The characteristics of the 46 included studies are described in eTable 1 (http://links.lww.com/CCX/B54). Most of the published literature was from Europe ( n = 18) (15–32), followed by Asia ( n = 12) (33–44), North America ( n = 9) (4, 45–52), South America ( n = 5) (5, 53–56), and Oceania ( n = 2) (57, 58). On the other hand, studies from North America contributed the highest number of patients ( n = 37,255), followed by South America ( n = 32,723), Asia ( n = 23,540), Europe ( n = 16,149), and Oceania ( n = 478).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the 46 included studies are described in eTable 1 (http://links.lww.com/CCX/B54). Most of the published literature was from Europe ( n = 18) (15–32), followed by Asia ( n = 12) (33–44), North America ( n = 9) (4, 45–52), South America ( n = 5) (5, 53–56), and Oceania ( n = 2) (57, 58). On the other hand, studies from North America contributed the highest number of patients ( n = 37,255), followed by South America ( n = 32,723), Asia ( n = 23,540), Europe ( n = 16,149), and Oceania ( n = 478).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-seven studies reported data on length of stay in the ICU (4, 5, 16–19, 21, 23–25, 28, 29, 32–36, 38–52, 54–58). The WM length of stay was 5.9 days (95% CI, 5.3–6.5 d), and the median was 5.7 days (range, 2.7–23.7 d).…”
Section: Resultsmentioning
confidence: 99%
“…Estudios publicados recientemente, refieren que la frecuencia de ingresos en la UCI por motivos neurológicos en pacientes con cáncer varía entre el 3% y el 23% [2], [3], [4], [5], [6].…”
Section: Introductionunclassified